Adaptation and Psychometric Evaluation of the Workplace Belongingness Scale in the Indonesian Context - Gita Widya Laksmini Soerjoatmodjo (Nusantara Journal of Behavioral and Social Science, 2026)
Workplace belongingness reflects an employee’s perception of being valued, supported, and fitting within the organizational environment. Although the Workplace Belongingness Scale (WBS) was originally conceptualized as a unidimensional construct, no validated Indonesian version has been available. This study aimed to adapt the WBS and examine its psychometric properties in an Indonesian working population. Following a forward–backward translation procedure, the 12-item instrument was administered to 292 employees from diverse organizational backgrounds. The dimensionality of the scale was evaluated using confirmatory factor analysis (CFA). The initial model indicated inadequate fit (CFI = 0.897; TLI = 0.874; RMSEA = 0.109; SRMR = 0.060). Model refinement was conducted by incorporating theoretically justified residual covariances based on priority 1 modification indices, resulting in improved but still marginally acceptable fit (CFI = 0.917; TLI = 0.897; RMSEA = 0.081; SRMR = 0.057). All standardized factor loadings were statistically significant. Internal consistency was high (ω = 0.905; α = 0.908). Overall, the findings provide preliminary support for the unidimensional structure of the Indonesian WBS following model refinement and for its internal consistency reliability. Further validation in independent samples is required.   Abstrak: Rasa memiliki di tempat kerja (workplace belongingness) merefleksikan persepsi pegawai mengenai sejauh mana mereka merasa dihargai, didukung, dan sesuai dengan lingkungan organisasi. Meskipun Workplace Belongingness Scale (WBS) pada awalnya dikonseptualisasikan sebagai konstruk unidimensional, hingga saat ini belum tersedia versi Bahasa Indonesia yang tervalidasi. Penelitian ini bertujuan untuk mengadaptasi WBS dan mengevaluasi properti psikometriknya pada populasi pekerja di Indonesia. Melalui prosedur forward–backward translation, instrumen yang terdiri dari 12 aitem diujikan kepada 292 pegawai dari berbagai latar belakang organisasi. Dimensionalitas skala dievaluasi menggunakan analisis faktor konfirmatori (CFA). Model awal menunjukkan kecocokan yang tidak memadai (CFI = 0.897; TLI = 0.874; RMSEA = 0.109; SRMR = 0.060). Penyempurnaan model dilakukan dengan memasukkan kovarians residual yang dijustifikasi secara teoretis berdasarkan modification indices prioritas 1, sehingga menghasilkan kecocokan model yang meningkat namun masih berada pada batas penerimaan (CFI = 0.917; TLI = 0.897; RMSEA = 0.081; SRMR = 0.057). Seluruh factor loadings terstandarisasi signifikan secara statistik. Reliabilitas internal tergolong tinggi (ω = 0.905; α = 0.908). Secara keseluruhan, temuan ini memberikan dukungan awal terhadap struktur unidimensional WBS versi Indonesia setelah proses penyempurnaan model, serta terhadap reliabilitas konsistensi internalnya. Validasi lebih lanjut pada sampel independen diperlukan.